PRONUNCIATION ERROR DONE BY THE STUDENT OF ISLAMIC EDUCATION IN STUDYING ABOUT ENGLISH PHONETICS AT THE FACULTY OF RELIGIOUS STUDIES IN THE UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA - Muhammad Rafii; Rahmadsyah Rangkuti (Hikari: Jurnal Bahasa dan Kebudayaan, 2022)
This article’s goals were to 1) look into what students thought about problems with phonetics learning, and 2) determine what elements were driving students' errors with phonetics learning. The samples consisted of 6 undergraduate Islamic education students who were chosen for an interview on purpose. A questionnaire and a semi-interview form were examined as research tools. According to the students' opinions, certain sounds, particularly [?], [ð], and [?], produced major phonetics learning challenges at the segmental level. It was also noted that linking produced major problems with supra segmental phonetics learning. Furthermore, phonetic ability was identified as the most common reason for difficulties in learning phonetics. It might be argued that the perception of the difference in sound systems between English and Indonesian, as well as various characteristics such as phonetic aptitude, native language, and prior English knowledge, all contribute to this conclusion.